PSVI-33 Queen bees' artificial breeding using selenium compounds. (5th December 2019) - Nevitov, Mikhail; Ostapchuk, Aleksandr; Poluboyarinov, Pavel; Gamayunov, Aleksey; Anipchenko, Polina; Stekolnikov, Anatoly; Plemyashov, Kirill; Baymishev, Khamidulla; Nikitin, Georgiy; Nechaev, Andrey; Melekhova, Irina; Rybin, Evgeniy; et al.
Abstract: The aim of the study was to research the effect of selenium-containing drugs on the efficiency of artificial hatching, using them in the composition of feeding of starter-families. The experiment was conducted in a private apiary located in the Penza region, Russia (30 bee colonies). The predominant honey plants - melilot, rose bay. The average productivity -65–70 kg of marketable honey.In the maternal family, 1.5-day-old larvae were taken, transferred to artificial pans and placed for a day in the family-starters, and then - in the queen-rearing colony. Families-starters once received a sugar syrup with selenium-containing drugs. Sugar syrup(S) was prepared in a 1: 1 ratio, selenium drugs were added to it. The introduction of selenopyran as part of top-dressing to the starter-family at a dose of 0.2 mg of selenium per 1 kg of bees causes an increase in selenium content in the body of bees by 138%, while the administration of sodium selenite and selenocystin does not lead to significant changes in the selenium status of insects under the same conditions.Sodium selenite, introduced as part of top-dressing to the family-starter up to 0.2 mg selenium per 1 kg of bee mass, increases the selenium content in the body of the queens that were in the 1st day of development in this family by 225%, while selenopyran with this method administration causes an increase in selenium level in the body of the uterus by 121%, and selenocystin - by 73%, compared with the control.The use of selenocystine and sodium selenite as part of feeding to starter families contributes to better preservation of the larvae in the development process in queen-rearing colony, compared with the control and provides a higher yield of queens (respectively, 214% and 157% higher).